BOARD DIVERSITY AND AUDIT QUALITY OF LISTED FOOD AND BEVERAGE FIRMS IN NIGERIA (Journal of Contemporary Issues in Accounting, 2023)
This study examined the effect of corporate board diversity on audit quality of listed food and beverage firms in Nigeria. Specifically, the objectives of the study are to; ascertain the effect of ethnicity diversity on audit quality, to determine the effect of age diversity on audit quality and to determine the effect of experience diversity on audit quality. Ex-post facto research design was adopted. The study was underpinned on agency and stakeholder’s theories. Formulated hypotheses were tested using Ordinary Least Square (OLS) statistical technique with the aid of SPSS version 20. Based on this, the study found out that ethnicity diversity and age diversity have no significant effect on audit quality of listed food and beverage firms in Nigerian Stock Exchange. In view of the findings of this study, it is observed that ethnicity diversity, age diversity and experience diversity do not significantly affect audit quality of listed food and beverage firms in Nigeria. The study recommended among others that ethnicity, age and experience diversities should not to be prioritized in corporate board composition.
Keywords: Corporate board diversity; Audit quality; listed food; beverage firms